2022
DOI: 10.1108/jedt-03-2022-0175
|View full text |Cite
|
Sign up to set email alerts
|

Shaping circular economy in the built environment in Africa. A bibliometric analysis

Abstract: Purpose This paper aims to explore the intellectual structure shaping the circular economy (CE) discourse within the built environment in Africa. Design/methodology/approach The study adopted a bibliometric analysis approach to explore the intellectual structure of CE in the built environment in Africa. The authors collected 31 papers published between 2005 and 2021 from the Scopus database and used VOSviewer for data analysis. Findings The findings show that there are six clusters shaping the intellectual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Circular economy is a fairly new concept in Africa, and there is growing interest in its potential as a tool for achieving sustainable development on the continent (Mhlanga et al, 2022). While Africa's circular economy is still in its early phases, there are numerous encouraging signals of improvement.…”
Section: Circularity In Africamentioning
confidence: 99%
“…Circular economy is a fairly new concept in Africa, and there is growing interest in its potential as a tool for achieving sustainable development on the continent (Mhlanga et al, 2022). While Africa's circular economy is still in its early phases, there are numerous encouraging signals of improvement.…”
Section: Circularity In Africamentioning
confidence: 99%
“…In contrast, CE research in the Global South is mainly unexplored (Muchangos, 2021), even more so in African countries and contexts (Mhlanga et al, 2022). Despite this, CE practices and initiatives exist in African countries at different levels of society.…”
mentioning
confidence: 99%
“…Similarly, the United Nations with Global Ghost Gear Initiative and other developed countries including India have already adopted the CE model (Gill and Verma, 2021). However, the concept is still novice in Africa (Mhlanga et al, 2022). Kenya (Muriithi and Ngare, 2023), South Africa (Republic of South Africa, 2020) and Nigeria (Olukanni et al, 2018) are among the few countries in Africa reported having policies and practices that align with CE.…”
Section: Challenges To Circular Economymentioning
confidence: 99%
“…The CE model serves as a countermeasure to the wasteful and unsustainable practices of the conventional LE model (Furkan, 2017;Gill and Verma, 2021). The CE paradigm is versatile and can be applied in numerous industries including seafood waste (Erasmus et al, 2021;Cooney et al, 2023), wastewater (Morseletto et al, 2022) and car manufacturing (Despeisse et al, 2015). The CE model aims at minimizing industrial waste while using resources sustainably (Principato et al, 2018;Gill and Verma, 2021).…”
Section: Introductionmentioning
confidence: 99%